Nationwide survey of Japanese breast oncology and reproductive endocrinology departments about the impact of breast cancer treatment on fertility. Issue 12 (15th October 2020) - Yamazaki, Rena; Ono, Masanori; Sugie, Tomoharu; Inokuchi, Masafumi; Ishikawa, Satoko; Iizuka, Takashi; Masumoto, Sakiko; Myojo, Subaru; Uchida, Soko; Horie, Akihito; Matsuzaki, Toshiya
Abstract: The purpose of this study is to assess the impact of breast cancer treatment on the reproductive potential. We conducted a nationwide survey of breast oncology and reproductive endocrinology and infertility (REI) departments using a questionnaire designed to assess the impact of breast cancer treatment on fertility. We received responses from 312 breast oncology departments (response rate, 31.9%) and 541 REI departments (response rate, 50.9%). The most common method of achieving pregnancy reported by breast oncology departments was natural insemination (69.6%), followed by assisted reproductive technology ( 15.6%) and intrauterine insemination (IUI; 14.8%). The most common method of achieving pregnancy reported by REI departments was conventional in vitro fertilization and/or intracytoplasmic sperm injection (51.0%), followed by natural insemination with or without ovulation induction (40.0%) and IUI (8.0%). The overall pregnancy rate for patients who underwent treatment for infertility at REI departments after breast cancer treatment was 39.0%. Vast patients who experienced breast cancer treatments conceived mainly by natural insemination based on the data from breast oncology departments. On the other hand, 61.0% of the patients who visited REI departments presumably due to infertility by natural insemination did not conceive even by infertility treatments with exclusive knowledge in REI departments.